PERBEDAAN INTENSI MENONTON PORNOGRAFI PADA SISWA SMA NEGERI 6 SEMARANG YANG MENJADI ANGGOTA ROHIS DENGAN YANG BUKAN ANGGOTA ROHIS - Tri Haryanto; Zaenal Abidin (Faculty of Psychology, Diponegoro University, 2014)
The aim of this study was to examine differences in the intentions of watching pornography on SMA Negeri 6 Semarang students between students who become members of Rohis with the non-member of Rohis. Intension of watching pornography is defined as the tendency of individuals to take action for seeing any form of image, video, or other forms of messages through various forms of communication media and/or performing in public, which contains obscenity or sexual exploitation. The population of this study was students of SMA 6 Semarang. Subjects in the study sample was divided into two groups, namely the group of students who are members of Rohis totaled 33 students and students who are not members of Rohis many as 57 students. The data was collected using the intention scale watching pornography (37 item). The intention scale watching pornography composed by aspects of the intentions of watching pornography. The aspects of the intention to watch pornography have been prepared on four aspects intentions which proposed by Ajzen (2005, p. 102) that is action, targets, context, and time coupled with the definition viewing behavior and the definition of pornography . The results show the value of t = 2.313 with p = 0.023 (p < 0.05) . These results indicate that there are significant differences in the intentions of watching pornography on SMA Negeri 6 Semarang students between students who become members of Rohis with the non-member of Rohis. Intension of watching pornography of SMA 6 Semarang students who are a member of Rohis lower than SMA 6 Semarang students who are not members Rohis .